Integrating Ethnopedagogy and Virtual Reality in Research-Based Learning for Regenerative Education - ., Mukhlis; ., Ariyatun; Septiana, Ika; ., Wijayanto; Arifianti, Ika (Journal of Cultural Analysis and Social Change, 2026)
This research aims to explore students' perspectives on the application of Ethnopedagogy-based Virtual Reality (Ethno-VR) in supporting regenerative education through a research-based learning approach. The research uses a quantitative approach with a comparative design, involving students from both science and non-science backgrounds. The data collection instrument was in the form of a questionnaire that measured learning engagement, understanding of local culture, ecological awareness, and perception of technological integration. Data were analyzed using ANOVA to see differences by field of study and gender. The results showed that science students had higher learning engagement (M = 21,100; SD = 2,654) compared to non-science (M = 18,615; SD = 3.709), with a significant tendency (F = 4.119; p = 0.052). Understanding of local culture was stronger in science students (M = 18,800) and women (M = 18,444), although the difference was not significant (F = 3,613; p = 0.067). Meanwhile, ecological awareness was significantly higher in science students (M = 17,860; F = 3.013; p = 0.047). On the other hand, the perception of technology integration was more appreciated by non-science students (M = 17,289) and women (M = 17,464), with ANOVA results being close to significant (F = 3,023; p = 0.052). In conclusion, Ethno-VR has the potential to strengthen the cognitive, affective, and ecological dimensions of students, although there are variations based on academic and gender backgrounds. The implications of this study emphasize the importance of integrating local wisdom-based technology in research-based learning to support the achievement of holistic regenerative education.